The Use of ICT and the Realistic Mathematics Education on Learning Functions to Develop Algebraic Thinking Skills - Dwi Antari Wijayanti; Hajizah, Mimi Nur (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2023)
The concept of function has evolved into one of the most fundamental principles in modern mathematics, influencing practically every area. However, it proved to be one of the most difficult ideas to grasp in mathematics. The concept of function is frequently taught without any connection to real-life situations. Students must work with problem scenarios that happen in a variety of contexts that are relevant to their everyday lives or make sense to them in order to gain authentic comprehension. This is consistent with the RME's properties. The unwillingness to highlight the visual element of the notion is one of the major roadblocks in learning functions. Using ICT and an RME approach to learning functions as an alternative to overcome these barriers could be a viable option. ICT and RME can help students learn mathematical principles in function content by providing a clearer visual experience. The purpose of this study is to investigate how ICT and RME can be used to improve learning function and increase algebraic thinking skills. This study conducted in a classroom of 29 junior high school students at the eighth grade. Design research methodology was used in this study by conducting three phases: preliminary design, teaching experiment, and retrospective analysis.